Hyperactivation of STAT3 is involved in abnormal differentiation of dendritic cells in cancer - Nefedova, Yulia; Huang, Mei; Kusmartsev, Sergei; Bhattacharya, Raka; Cheng, Pingyan; Salup, Raoul; Jove, Richard; Gabrilovich, Dmitry (The Journal of immunology (1950), 2004)
Abnormal differentiation of myeloid cells is one of the hallmarks of cancer. However, the molecular mechanisms of this process remain elusive. In this study, we investigated the effect of tumor-derived factors on Janus kinase (Jak)/STAT signaling in myeloid cells during their differentiation into dendritic cells. Tumor cell conditioned medium induced activation of Jak2 and STAT3, which was associated with an accumulation of immature myeloid cells. Jak2/STAT3 activity was localized primarily in these myeloid cells, which prevented the differentiation of immature myeloid cells into mature dendritic cells. This differentiation was restored after removal of tumor-derived factors. Inhibition of STAT3 abrogated the negative effects of these factors on myeloid cell differentiation, and overexpression of STAT3 reproduced the effects of tumor-derived factors. Thus, this is a first demonstration that tumor-derived factors may affect myeloid cell differentiation in cancer via constitutive activation of Jak2/STAT3.